Book Reviews - Pitt, Malcolm S. (The Muslim world, 1957)
Book Reviews in This Article: Humor in Early Islam. By Franz Rosenthal. Persian oil, A Study in Power Politics. By L. P. Elwell-Sutton. Changing Society in India & Pakistan. A study in Social Change and Social Stratification. By A. K. Nazmul Karim. A History of South-East Asia. By D. G. E. Hall. Heritage of Islam. By K. Jamil Ahmed. Mission on the Nile. By James Dempsey. The Middle East: Its Religion and Culture. By E. J. Jurji. Social Implications of Industrialization and Urbanization in Africa South of the Sahara. Mid-East: World Center. Edited by Ruth Nanda Anshen.